The Sensitivity of Male Labor Supply Estimates to Choice of Assumptions - DaVanzo, Julie; Tray, Dennis N. De; Greenberg, David H. (The Review of Economics and Statistics, 1976)
The task is an analysis of the traditional labor supply model using several competing methodologies. The approach is a step-by-step exploration of alternative labor supply estimating equations that attempts to identify the independent (marginal) effect of each particular change in the form of these equations. By systematically exploring what difference each of these changes makes to the parameter estimates, one can isolate which factors strongly affect estimated response parameters. Results from existing research can then be evaluated within a larger context, and future research can concentrate on resolving those methodological issues that do make a difference.